OIMS basic documentation: Technical documentation of the OIMS Base self-describing metadata schema, the high-level OIMS structure and their validation schemas. OIMS version 2.4 - Kruseman, Gideon; Laporte, Marie-Angelique (2023)
The Open Ontology-Based Interoperable Information Asset Metadata Schema (OIMS) is a flexible and extensible metadata schema designed to standardize and organize metadata for various information assets like datasets, documents, models, and publications, making them more accessible, transparent, and reusable. The purpose of this document is to provide the technical documentation for the self-describing metadata schema at the core of OIMS. This technical documentation is intended for its primary audience of metadata schema developers and related tool developers. OIMS is a comprehensive and structured approach to managing and organizing valuable information assets. Designed with a strong foundation in ontology, OIMS ensures efficient organization and retrieval of data resources within complex information systems. By leveraging standardized metadata schema, OIMS promotes interoperability, consistency, and clarity across various data domains. Its adaptable and extensible structure allows for seamless integration into a wide range of applications, empowering organizations to harness the full potential of their information assets and drive data-driven decision-making processes. This technical documentation is limited to the self-describing metadata schema and the high-level structure of any OIMS-compatible metadata file and includes the JSON schema validation files.